PENGARUH WORD OF MOUTH (WOM), KUALITAS PELAYANAN, KEAMANAN DAN KEPERCAYAAN TERHADAP KEPUTUSAN KONSUMEN MENGGUNAKAN JASA TRANSPORTASI ONLINE GRABBIKE DI KOTA SURAKARTA - Yasmin Rajaa Nabilah; Andri Nurtantiono (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study was to determine the effect of Word of Mouth, Service Quality, Security, and Trust on Consumer Decisions using GrabBike Online Transportation Services in Surakarta City. From distributing questionnaires to 100 respondents, results show that Word of Mouth, Service Quality, and Trust have a significant effect on consumer decisions while security has no significant effect on consumer decisions. Keywords: Consumer Decisions, Word of Mouth, Service Quality, Security, Trust